Pengaruh Kompetensi Pedagogik Dosen terhadap Prestasi Akademik Mahasiswa Universitas Patompo - Yunus, Irham Maulana; Aisyah T, A. Indira Nurul (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to analyze the influence of lecturers’ pedagogical competencies on students’ level of understanding in Social Studies courses at Patompo University. The research used a quantitative approach with an ex post facto method. The population of the study was 30 students taking Social Studies courses, simultaneously made as a sample by saturation sampling technique. The research instrument took the form of a Likert-scale questionnaire measuring lecturers’ pedagogical competence and students’ level of understanding, complemented by grading documentation. Data were analyzed using simple linear regression and t tests. The results of the study showed that the lecturers’ pedagogical competence positively and significantly affected the students’ level of understanding, with values of R = 0.742 and R2 = 0.513. The t-test resulted in t count = 5.432 t table = 2.048 at α = 0.05, which means the hypothesis was accepted. These findings indicate that improving lecturers’ pedagogical competencies can strengthen students’ understanding of lecture material.